Changing attitudes and perceptions of hispanic men ages 18 to 25 about rape and rape prevention - Lawson, Sarah Lynn (2012)
This exploratory study was designed to test the effectiveness of Foubert's intervention, The Men's Program, on a sample of 18- to 25-year-old Hispanic men who are not enrolled at a University or College. We explored participants’ perceptions of, reactions to, and experience of the program. The information collected will be used to adapt the program to this specific population in order to increase cultural relevancy and specificity and create lasting attitudinal change. Three groups of six-eight Hispanic males (n = 22) were exposed to the intervention program. The Bystander Attitude Scale and the Rape Attitude and Beliefs Scale were administered as pre- and post-test measures. A short focus group was conducted to ask the men about their experience of the intervention. Analysis showed a significant increase in participants’ willingness to intervene (p = 0.005) along with a decrease in rape myth acceptance in four of the five subscales (Justice p = 0.03; Status p = 0.004; Tactics p = 0.04; and Gender p = 0.002) after exposure to the intervention. Analysis of focus group material yielded several interesting themes about knowledge of rape, family and culture, perceptions of women, and the program material. This study showed promising change in attitudes about rape beliefs and bystander behaviors in Hispanic males exposed to an educational intervention. Through the information obtained, a cultural adaption from the analysis of the focus group data will be implemented during Phase 2 of the study. The adapted intervention will be tested before, after, and 1- and 3-months post-intervention to test whether the change in attitudes and behaviors are sustainable over time.